2013
DOI: 10.1111/epi.12378
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor antagonist NBQX attenuates later‐life epileptic seizures and autistic‐like social deficits following neonatal seizures

Abstract: Summary Purpose To determine whether AMPA receptor (AMPAR) antagonist NBQX can prevent early mTOR pathway activation and long-term sequelae following neonatal seizures in rats, including later-life spontaneous recurrent seizures, CA3 mossy fiber sprouting, and autistic-like social deficits. Methods Long-Evans rats experienced hypoxia-induced neonatal seizures (HS) at postnatal day (P)10. NBQX (20 mg/kg) was administered immediately following HS (every 12h x 4 doses). 12h post-HS, we assessed mTOR activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
83
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 71 publications
(149 reference statements)
12
83
1
Order By: Relevance
“…This, however, does not argue against the possibility that they represent electrographic seizures. Monomorphic focal EEG seizures are not uncommon in patients with different types of epilepsy30, 31, 32 and have also been described in other animal models of acquired epilepsy, such as the perinatal hypoxia model of epilepsy 33, 34. Furthermore, the fact that HVSWs can be suppressed by rapidly acting ASDs such as DZP as shown by Klein et al10 in FVB/N mice and here for NMRI mice would be consistent with a nonconvulsive seizure definition as shown in Table 4.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This, however, does not argue against the possibility that they represent electrographic seizures. Monomorphic focal EEG seizures are not uncommon in patients with different types of epilepsy30, 31, 32 and have also been described in other animal models of acquired epilepsy, such as the perinatal hypoxia model of epilepsy 33, 34. Furthermore, the fact that HVSWs can be suppressed by rapidly acting ASDs such as DZP as shown by Klein et al10 in FVB/N mice and here for NMRI mice would be consistent with a nonconvulsive seizure definition as shown in Table 4.…”
Section: Discussionsupporting
confidence: 82%
“…However, such EEG events in sham controls were only observed in rats at 7–8 months of age and not in younger rats 40. Similarly, intermittent low‐frequency epileptiform discharges were recorded via hippocampal depth electrodes in control rats 33, 34. However, as in the studies in mice, these SLEs in rats were clearly different in several aspects, including morphology, incidence, and frequency, from those in models of acquired epilepsy in rats 33, 34, 40.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a follow-up study, Rakhade et al (2011) stained the Fluoro-Jade B, a high affinity fluorescent marker for neuronal degeneration and confirmed the absence of neuronal death and degeneration at 24-48 h following hypoxic seizures at P10. Hippocampal mossy fiber sprouting has been known as a common feature of human temporal lobe epilepsy and observed in numerous neonatal seizure models (Anderson et al, 1999;Babb, 1991;Holmes et al, 1999;Lippman-Bell et al, 2013;Mathern et al, 1996;Rakhade et al, 2011;Sogawa et al, 2001). Furthermore, it has been suggested to play an important role in hippocampal neuronal hyperexcitability and epileptogenesis (Wuarin and Dudek, 1996).…”
Section: Neuropathology and Histology Changesmentioning
confidence: 99%
“…Furthermore, it has been suggested to play an important role in hippocampal neuronal hyperexcitability and epileptogenesis (Wuarin and Dudek, 1996). Timm staining is usually used to evaluate hippocampal mossy fibers Holmes et al, 1999;Huang et al, 1999;Lippman-Bell et al, 2013;Rakhade and Jensen, 2009;Rakhade et al, 2011). Using neonatal hypoxic seizure model in rats, we have recently shown that hypoxia-induced seizures in the immature brain lead to significant increases in CA3 mossy fiber sprouting later in life as evidenced by increased Timm staining (Lippman-Bell et al, 2013;Rakhade et al, 2011).…”
Section: Neuropathology and Histology Changesmentioning
confidence: 99%